Peningkatan Ekonomi Kelompok Tani Melalui Pendampingan Budidaya dan Proses Pasca Panen Kopi Robusta di Desa Wanatirta Kecamatan Paguyangan - Siti Badiatul Umroh; Sutarmin; Melina Azqia; Hendi Nazarudin Latif (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Wanatirta Village, located in Paguyangan District, Brebes Regency, has significant potential for robusta coffee cultivation. However, productivity has declined due to improper farming techniques and limited supporting equipment. Traditional harvesting methods have resulted in inconsistent bean quality and low selling prices. This Community Service Program aims to enhance farmers’ capacity through training in modern cultivation techniques, coffee tree rejuvenation using cutting methods, and the introduction of post-harvest technologies such as drying, hulling, and sorting. The activities include problem identification, training implementation, mentoring, and evaluation, with active participation from farmer groups. The results show improved farmers’ knowledge and skills, the adoption of robusta coffee quality standards, and better management within farmer groups